Mental health risks of health professionals who worked on the front lines against the new coronavirus: narrative review (Research, Society and Development, 2022)
Infection with the new coronavirus has become a public health emergency. Health professionals were asked to act in defense against the new virus. This resulted in duplicate working hours, isolation and insecurities, factors that put the mental health of these professionals at risk. The purpose of this narrative review is to present results from publications on the mental health dangers of health professionals working on the front lines against COVID-19. Articles were searched at PubMed Central, Scopus and Virtual Health Library. Found articles 92. After analysis, 12 articles were selected. The main frustrations experienced by the professionals were lack of PPE, isolation, risk of contracting the virus, feeling of incapacity and long working hours. The professionals also had anxiety, insomnia, stress, depression, panic and muscle pain. The mental health of health professionals is compromised, and may put the capacity for professional performance at risk in the future.